1998
DOI: 10.1111/j.1469-7793.1998.103by.x
|View full text |Cite
|
Sign up to set email alerts
|

An intercellular regenerative calcium wave in porcine coronary artery endothelial cells in primary culture

Abstract: A regenerative calcium wave is an increase in cytosolic free calcium concentration ([Ca2+]i) which extends beyond the stimulated cells without decrement of amplitude, kinetics of [Ca2+]i increase and speed of propagation. The aim of the present study was to test the hypothesis that such a wave could be evoked by bradykinin stimulation and by scraping cultured endothelial cells from porcine coronary arteries. Calcium imaging was performed using the calcium‐sensitive dye fura‐2. A wound or a delivery of bradykin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 39 publications
(25 reference statements)
1
35
2
Order By: Relevance
“…However, based on our Ca 2 þ response data, we cannot exclude that the endothelial cells might also express mibefradil-sensitive Ca 2 þ channels. The current view is that endothelial cells do not express voltagedependent Ca 2 þ channels (Domenighetti et al, 1998;Nilius & Droogmans, 2001), although the opposite has also been suggested (Vinet & Vargas, 1999;Wu et al, 2003).…”
Section: Basal Characteristics Of the Kcl-induced Ca 2 þ Responsementioning
confidence: 87%
“…However, based on our Ca 2 þ response data, we cannot exclude that the endothelial cells might also express mibefradil-sensitive Ca 2 þ channels. The current view is that endothelial cells do not express voltagedependent Ca 2 þ channels (Domenighetti et al, 1998;Nilius & Droogmans, 2001), although the opposite has also been suggested (Vinet & Vargas, 1999;Wu et al, 2003).…”
Section: Basal Characteristics Of the Kcl-induced Ca 2 þ Responsementioning
confidence: 87%
“…To examine effects of gap junction inhibitors on "baseline" vascular tone and hypoxic vasoconstriction in meclofenamate-and L-NNA-pretreated normotensive and hypertensive lungs, 30 M 18␣-glycyrrhetinic acid (Sigma) (10,29), 50 M palmitoleic acid (Sigma) (3,13,27,56), or vehicle (DMSO) was added to the perfusate according to the above protocol for CYP450 inhibitors. The lungs were then challenged twice with 15 min of 3% O 2 at 15 and 40 min after the gap junction inhibitors or vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…The incidence of myoendothelial gap junctions is higher in resistance than in conduit arteries (46). Putative gap junction inhibitors, such as palmitoleic acid (13,27,56), 18␣-glycyrrhetinic acid (10,16,23,27,29,36,52,53), and Gap 27 (9,16,47,52), a synthetic peptide with sequence homology to a region of the second extracellular loop of Cx37 and Cx43, reduce EDHF-mediated hyperpolarization and relaxation in various arteries. These observations suggest that the EDHF signal represents electrotonic spread of hyperpolarization from the endo-thelium into the medial smooth muscle via myoendothelial and homocellular smooth muscle gap junctions.…”
mentioning
confidence: 99%
“…Although this could be influenced by the choice of model or anestethic agent, we would argue that conducted hyperpolarizations along the endothelial pathway leading to remote dilatations, cannot explain the phenomenon of CSDs. Much slower intercellular Ca 2 þ waves have been described in ECs in culture, 89 in isolated vessels, 17 and in vivo. 16 The intercellular Ca 2 þ waves are dependent on the PLC pathway, IP 3 diffusion, Ca 2 þ -induced Ca 2 þ release, and gap junctions.…”
Section: Potential Role Of Vascular Conducted Responses In Cerebrovasmentioning
confidence: 99%